The Jarimatics Method in Improving Students' Numeracy Skills - Afrina Maya Febryanti; Uki Suhendar; Wahyudi Wahyudi (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2023)
This study explores students' understanding before and after applying the jarimatics method in learning mathematics, considering Islamic educational models or perspectives. This objective involves understanding how the jarimatics method can enrich an Islamic education-based learning approach and identifying its impact on improving students' numeracy skills in basic number operations. The research method uses quantitative research. The number of subjects is 20 grade 1 students of PPWNI Klang divided into two experimental groups of 10 and a control group of 10. This study's results indicate that the experimental group's posttest average value is 90.70 higher than the value of the control group, which is 81.50. Based on the t-test, a significance of 0.000 < 0.05 indicates a significant effect on applying the Jarimatics Method to the numeracy skills of grade 1 students. PPWNI Klang, Selangor Malaysia. The jarimatics method provides an approach that is easy to understand, does not burden students' thinking power, and provides certainty in mathematical calculations. The results of this study also support the opinions of experts and previous data modelling, which show the benefits of the jarimatics method in the context of learning mathematics. By paying attention to aspects of Islamic education in the Jarimatics method, this approach becomes relevant and valuable to develop quality students' understanding of mathematics by paying attention to spiritual and moral aspects of the learning process.